2014
DOI: 10.1188/14.cjon.s1.26-30
|View full text |Cite
|
Sign up to set email alerts
|

Translating Research on the Distress Thermometer Into Practice

Abstract: Distress is commonly experienced by people with cancer. The National Comprehensive Cancer Network (NCCN) developed a guideline for screening and managing distress in 1999 and has updated the guideline on an annual basis ever since. Using the five-phase framework for translational research, this article summarizes research findings related to the guideline and associated distress thermometer for each phase of translational research. The NCCN Distress Management Guideline is a useful tool to screen for and manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Also, item-level correlation analyses showed significant correlations between symptoms, financial difficulties, work/daily activities, and cognitive function. Others have examined the DT with respect to the HADS, 12,[16][17][18] and our study complements that research by examining the DT in relation to other dimensions of HRQoL. Research in psycho-oncology has made evident that cancer care involves more than clinical treatment of the disease, and patients' experiences of psychosocial concerns has gained a greater attention within the cancer community.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Also, item-level correlation analyses showed significant correlations between symptoms, financial difficulties, work/daily activities, and cognitive function. Others have examined the DT with respect to the HADS, 12,[16][17][18] and our study complements that research by examining the DT in relation to other dimensions of HRQoL. Research in psycho-oncology has made evident that cancer care involves more than clinical treatment of the disease, and patients' experiences of psychosocial concerns has gained a greater attention within the cancer community.…”
Section: Discussionmentioning
confidence: 64%
“…Several studies 12,16,17 have tested the validity of the DT with the Hospital Anxiety and Depression Scale (HADS), also using HADS to determine specificity and sensitivity for identifying clinical cases. 18 Based on a validation study examining a Swedish translation of an earlier version of the DT (version 1.2004) in relation to HADS, Thalén-Lindström et al 17 suggested that, with a cutoff threshold for significance of ≥4, the DT is valid for screening purposes and has the ability to measure changes in distress over time.…”
mentioning
confidence: 99%
“…Many cancer survivors have moderate to severe unmet needs, often as consequences of treatment (Carey et al 2012 ). Changing the way cancer survivors are supported remains an ongoing priority (Tavernier 2014 ). Much of this work has focused on better understanding and acting on people’s individual holistic needs (Rooney et al 2014 ), and various tools and strategies have been developed to facilitate this agenda (Henry et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Their mental status was assessed using the National Comprehensive Cancer Networkrecommended Distress Thermometer (8). A self-evaluation of mental distress, this tool includes 11 items that are scored on a scale ranging from 0 to 10, where 0= no stress and 10= extreme stress.…”
Section: Clinical Outcomesmentioning
confidence: 99%